Pathology of Septicaemic Colibacillosis in a Guniea Fowl Breeder Flock - P.Srinivasan; T.R.G.Murthy; K.Gopal; S.Saravavan; V.Gowthaman (The Indian Veterinary Journal, 2024)
Guinea fowl meat and eggs are tastier and rich in nutritional values. Moreover these birds are resistant to many poultry diseases which affect other poultry species, hence easier to manage by farmers with little health facilities.Due to the intensive production system followed now a days, Guinea fowls are susceptible to various infectious and non-infectious diseases. However, meager information was available on the prevalence of diseases in guinea fowl which isessential in order to minimize the economic losses associated with it. The present study was undertaken to determine the cause of increased mortality in an intensively maintained 1300 guinea fowl breeder flock of 17 week old during the month of August 2023. Necropsy examination conducted on dead birds and samples collected were subjected for bacteriological and pathological examination. Affected Guinea fowl breeder flock showed the clinical signs ofdepression, anorexia, pasted vents and marked respiratory soundswith a cumulative mortality of 9.2 per cent over the period of two weeks. At necropsy, dead birds showed good body condition, fibrinous pericarditis, congestion of lungs, greenish discolouration of liver and moderated enlargement with mottled appearance of spleen. Microbiological examination of heart blood and liver swab revealed the presence ofEscherichia coli. The flock was successfully treated with levofloxacin (@ 10mg/kg B.wt) based on the antibiotic sensitivity test. Microscopically, fibrinous pericarditis, myocardial degeneration in heart, vascular changes in lungs, acute cellular degeneration and vascular changes with infiltration of inflammatory cells in liver and lymphoid depletion and reticuloendothelial cells proliferation in spleen were noticed. In conclusion, intensively maintained guinea fowls are susceptible to E.coli infection similar to that of other poultry species.